SNOW TRANSPORT EQUIPMENT MODEL 40 TOWED SNOWPLOW CARRIER. - Hansen,R. W. (1965)
A 40-foot-long ski-mounted snowplow carrier, designed for towing, was developed to eliminate pitching and rolling of the snowplow on deep snow and to permit uniform removal of snow from borrow pits, compacted-snow areas, and ice. The carrier includes two grader blades which funnel the snow into the feeder box of a rotary snowplow. These blades are hydraulically controlled for leveling or plowing. Two prototype snowplow carriers, towed by Size 2 tractors, were used near McMurdo, Antarctica, during Deep Freeze 64 and 65 for transporting fill snow to elevate a 150by 6,000-foot experimental compacted-snow runway and a 3-mile-long road. They were also used for cleaning drift snow from the experimental compacted-snow runway and the operational sea-ice runway. In these operations, snow was cast up to 100 feet at rates up to 2,000 cubic yards per hour. It was concluded that the Model 40 snowplow carrier is suitable for elevating roads and runways on deep snow and for clearing drift from compacted snow and ice. It should be included in the equipment allowance for polar installations on snow. (Author)